Effect of isonuclear-alloplasmic cytoplasmic male sterility system on grain yield traits in pearl millet - Pujar, Mahesh; Govindaraj, Mahalingam; Gangaprasad, S.; Kanatti, A. (Indian Society of Genetics & Plant Breeding, 2019)
Pearl millet is a nutri-cereal and is grown predominantly by subsistence farmers in semi-arid regions of India and Africa. Considering it’s highly cross pollinated nature and availability of cytoplasmic male sterility (CMS), hybrids have become a dominant cultivar type in India. Present study aims to assess the effect of isonuclear alloplasmic A1 , A4 and A5 CMS on agronomic performance of pearl millet hybrids. Five isogenic females each having 3 alloplasmic (A1, A4 and A5) cytoplasm were crossed with 6 male-parents to generate 120 hybrids. All these were evaluated in two contrasting seasons (E) in split-split-plot design. The significant cytoplasm per se and restorer per se indicate the both contribution to most of the traits, however, greater magnitude of contribution arises from restorers significantly (75% grain yield; 95% 1000-grain weight). The significant, hybrids x E shows the mandatory of multilocation testing for yield traits while non-significant of CMS × E interaction reveals the greater stability of CMS. Further, non-significant mean yield differences exhibited in A1, A4 and A5 hybrids (2.84-3.14 t ha–1) indicated no adverse effect of cytoplasm on grain yield and associated traits. Also, diverse genetic backgrounds used in this study displayed significant contributions to grain yield and its component traits. These results imply the prospects for utilization of potential alternative cytoplasm (A4 and A5) to widen the cytoplasm base together with development of counterpart restorers to produce future high-yielding hybrids.